Response and Resistance to MEK Inhibition in Leukaemias Initiated by Hyperactive Ras - Lauchle, Jennifer O. (2009)
The Raf/MEK/ERK cascade is a therapeutic target in human cancers with deregulated Ras signaling, which includes tumours that have inactivated the Nf1 tumour suppressor(1). Nf1 encodes neurofibromin, a GTPase activating protein that terminates Ras signalling by stimulating hydrolysis of Ras•GTP. We compared the effects of inhibitors of MEK in a myeloproliferative disorder (MPD) initiated by inactivating Nf1 in mouse bone marrow and in acute myeloid leukaemias (AMLs) in which cooperating mutations were induced by retroviral insertional mutagenesis. Here we show that MEK inhibitors are ineffective in MPD, but induce objective regression of many Nf1-deficient AMLs. Drug resistance developed due to outgrowth of AML clones that were present before treatment. We cloned clone-specific retroviral integrations to identify candidate resistance genes including Rasgrp1, Rasgrp4, and Mapk14, which encodes p38α. Functional analysis implicated increased RasGRP1 levels and reduced p38 kinase activity in resistance to MEK inhibitors. This approach represents a robust strategy for identifying genes and pathways that modulate how primary cancer cells respond to targeted therapeutics and for probing mechanisms of de novo and acquired resistance.